Educating Children with Autism Spectrum Disorders (ASDs) to Delay Gratification in the Contet of Temper Tantrums - Seungyeon Lee (The Advocate, 2014)
Temper tantrums among young children are common, especially those with autism spectrum disorders. Delay of gratification is an essential component of temper tantrums. Teachers and parents seek management strategies for temper tantrums that are efficient, effective and ethical. The purpose of this applied behavioral analysis research was to compare various types of functional communication training with three children in the three and a half year old age range. In Phase One, to determine the misguided goal or function of each child’s temper tantrum, functional behavioral assessment was undertaken. In Phase Two, a reward menu was used to determine preferred rewards for the treatments. In Phase Three, a multiple baseline across participants design was used to reduce temper tantrums and increase appropriate communication that was identified through functional communication training (FCT). In Phase Four, fixed time delay (FD), progressive time delay with verbal praises (PDVP) and progressive time delay with visual cues (PDVC) were employed to represent three intervention conditions to teach delay of gratification. In Phase Five, parents were surveyed to determine the social validity or acceptability of the interventions with parents. Two independent observers counted frequency of temper tantrums, frequency of alternative communication behaviors, and length of wait time in each of these three children. Results showed that progressive time delay with visual cues (PDVC) increased wait time and reduced temper tantrums the most. Implications for teachers and parents working with young children prone to temper tantrums are discussed.